Credibility in Female Consumer Engagement: An Examination of Influencer Influence on Purchasing Local Muslim Fashion Brands in Batam Islands - Putra, Edy Yulianto; Hapsari, Ratih Regina; Ariyanto, Hepy Hefri (Universitas Islam Kadiri, 2026)
Purpose – This study aims to analyze the influence of authenticity of influencer credibility (influencer credibility), and Electronic Word of Mouth (e-WOM) on consumer purchase intention (purchase intention) of local Muslim fashion products, with influencer authenticity as a mediating variable. Methodology – This study uses a quantitative approach with a survey method on 312 respondents who have purchased local Muslim fashion products. The analysis was conducted using the Partial Least Squares Structural Equation Modeling (PLS-SEM) approach using SmartPLS 4.0 software. Findings – The research findings revealed that Influencer authenticity, influencer credibility, and content engagement directly stated a very strong positive effect on consumer purchase intention. In addition, influencer authenticity was also proven to be able to mediate the significant relationship between E-WOM, influencer credibility, and content engagement on purchase intention. Originality/Novelty – The novelty of this study lies in the mediating role of influencer factors in influencing purchase intentions in the local Muslimah fashion industry, which has not been widely researched. Implications – The implementation of marketing strategies through E-WOM, influencer credibility, and content engagement will be more effective in encouraging purchase intentions if delivered through an influencer figure who is considered authentic by the audience.